Karakteristik Fisikokimia dan Sensoris Selai Lembaran Labu Kuning dengan Penambahan Tepung Porang - Puspitasari, Estiana; Wulandari, Yuni Dyah; Nurrahman; Sya'di, Yunan Kholifatuddin; Yonata, Diode (Pro Food, 2025)
Sheet jam is one of the modified spread jam products made in sheet form. One of the food ingredients that can be processed into sheet jam is pumpkin. Pumpkin contains various chemical compounds, such as vitamin A, vitamin C, antioxidants, β-carotene, and phenol. In making pumpkin sheet jam, it is necessary to add hydrocolloids that can improve the physical properties of the resulting sheet jam, one of which is porang flour. The purpose of this study was to determine the effect of adding porang flour on the physicochemical and sensory characteristics of pumpkin sheet jam. The design used in this study was a completely randomized design with a single factor consisting of 5 treatments (0, 1, 2, 3, and 4%). The research procedure began with making pumpkin puree and making sheet jam with a drying time of 6 hours. The results showed that the addition of porang flour with different concentrations had a significant effect on tensile strength, color, vitamin C content, total phenol, antioxidant activity, β-carotene content, and sensory properties (color and texture), but did not affect taste and flavor. The higher the concentration of porang flour added to the pumpkin sheet jam, the higher the tensile strength value and the darker the yellowish color, but the levels of vitamin C, total phenols, antioxidant activity, and β-carotene decreased.